Exploring the Role of Parental Involvement and its Effects on Student Performance in Rural Schools - Estor, Jayzon R.; Lantaka, Ivy A. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examined the influence of parental involvement on the academic performance of Grade I to III pupils at Campo Uno Elementary School, a rural school in Zamboanga City that serves Indigenous Subanen learners. The research was guided by Epstein’s Framework of Parental Involvement and explored three main dimensions: school participation, the provision of educational resources, and academic support given at home. A descriptive-correlational research design was used, and data were collected from 74 parents through validated survey questionnaires. The findings revealed that parental involvement was generally low across all dimensions. Many parents rarely participated in school activities, had difficulty providing necessary learning materials, and offered limited academic support at home. The students, on the other hand, achieved an average grade of 78.81, which falls within the "Fairly Satisfactory" range. Statistical analysis showed no significant relationship between parental involvement and academic performance. Additionally, no meaningful differences were found when parental involvement was analyzed based on demographic factors such as age, gender, income, and educational background. These results suggest that in rural communities like Campo Uno, factors such as poverty, limited access to resources, and cultural barriers may hinder parents from engaging more fully in their children’s education. The study recommends that schools develop inclusive and practical strategies that promote family-school partnerships, especially in underserved and indigenous communities where support systems are often lacking.